Manipulation of the In Situ Nitrogen‐Vacancy Doping Efficiency in CVD‐Grown Diamond. Issue 10 (31st March 2022) - Langer, Julia; Cimalla, Volker; Lebedev, Vadim; Kirste, Lutz; Prescher, Mario; Luo, Tingpeng; Jeske, Jan; Ambacher, Oliver
Abstract : Herein, the in situ generation of nitrogen‐vacancy (NV) centers in diamond during chemical vapor deposition (CVD) is investigated depending on the electric‐field strength at the sample position. The alteration of the electric‐field strength is induced by changing the resonance conditions within the resonator cavity while keeping the growth input variables constant. The electric‐field strength distribution is obtained by simulation results. During the growth experiments, optical‐emission spectroscopy data is collected, which shows the impact of the electric‐field strength on the radical concentrations within the plasma and the gas temperature. Through the reduction of the electric‐field strength, the synthesis of thick, high‐quality, nitrogen‐doped diamond without the formation of a polycrystalline rim around the sample edges and the twinning‐induced growth of polycrystalline grains was accomplished. Therefore, a reduced internal and more homogeneous stress distribution is achieved. Furthermore, significant influences on the in situ NV doping are discovered. In addition to a considerable gain of the in situ NV generation, also a major enhancement of the in situ incorporation efficiency of NV centers in comparison to N s 0 centers up to almost 3% is observed. Depending on the application, this makes posttreatment processes for additional NV generation dispensable. Abstract : Diamonds exhibiting a high nitrogen‐vacancy (NV) density are of interest for quantum technological applications. Especially, in situ–generated NV centers are known to exhibit outstanding quantum properties. Hence, it is imperative to increase the in situ NV‐doping efficiency in CVD‐grown diamonds. Herein, a major enhancement of around 3% NV to Ns 0 is presented.